Social Presence and Purchase Intention In Live Streaming Shopping: Mediating Role Of Trust and Psychological Distance - Mishra, Udgam (Indonesian Journal Publisher, 2025)
The study examines the interconnected relationships between social presence, trust, psychological distance, and purchase intention for live-streaming shopping. Using a survey of 390 live-streaming shopping consumers based in Nepalese urban areas the study analyzed relationships between variables. The research data was gathered through structured surveys which later underwent structural equation modelling (SEM) analysis for testing the proposed relationships. Research findings demonstrate how social presence boosts consumer trust illustrating the necessity of personal connections to establish trust within online transactions. The presence of social elements failed to minimize psychological distances between consumers or affect their purchase intentions directly. The research results showed no support for trust and psychological distance as mediators between social presence and purchase intention. The study shows that social presence remains vital for developing consumer trust yet alternative factors such as emotional connection and perceived value surpass it in influencing actual purchase intentions within live-streaming shopping platforms. This study presents meaningful findings to market researchers and provides guidance for upcoming investigations in modern online buying domains.